2010
DOI: 10.2350/09-12-0771-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrops Fetalis in the Stillborn: A Series from the Central Region of Thailand

Abstract: The purpose of this study was to analyze the cause of hydrops fetalis (HF) among fetal deaths in the central region of Thailand. Autopsy reports diagnosed as HF from 1999 to 2008 at King Chulalongkorn Memorial Hospital were retrieved, and the pathologic findings, clinical information, fetal ultrasonographic studies, and laboratory investigations were reviewed. There were 78 stillborn autopsies during this 10-year period; the mean gestational age was 28 weeks. The causes of fetal hydrops were identified in 88.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
(49 reference statements)
1
30
1
3
Order By: Relevance
“…The mean gestational ages in these 3 groups were not signiflcantly different (P = 0.19). Some of the cases with hydrops fetalis have been previously published (8).…”
Section: Resultsmentioning
confidence: 99%
“…The mean gestational ages in these 3 groups were not signiflcantly different (P = 0.19). Some of the cases with hydrops fetalis have been previously published (8).…”
Section: Resultsmentioning
confidence: 99%
“…In a study from Thailand, 16 % of stillborn fetuses were hydrops fetalis, and the most common cause of hydrops was anemia [ 9 ]. In two other autopsy studies from Rodriguez, frequency of hydrops was 6.07 % in stillbirth cases and 7.45 % in neonatal death cases [ 220 ].…”
Section: Pathological Findingsmentioning
confidence: 99%
“…Not surprisingly, the study from Thailand [ 9 ] showed more hematological causes, as thalassemia is common in that part of the world. [ 11 , 40 -212 ] …”
Section: Causes and Mechanisms Of Fetal Hydropsmentioning
confidence: 99%
“…Some hemo globinopathies, such as Hb Bart, result in extreme hypoxia, and such model cases are important to include when validating a grading system that reflects fetal hypoxia. We therefore took advantage of the fact that Hb Bart has a high prevalence in Thailand [15].…”
Section: Introductionmentioning
confidence: 99%